A novel endpoint for exacerbations in asthma to accelerate clinical development: a post-hoc analysis of randomised controlled trials. Issue 7 (July 2017) - Fuhlbrigge, Anne L; Bengtsson, Thomas; Peterson, Stefan; Jauhiainen, Alexandra; Eriksson, Göran; Da Silva, Carla A; Johnson, Anthony; Sethi, Tariq; Locantore, Nicholas; Tal-Singer, Ruth; Fagerås, Malin
Summary: Background: Occurrence of severe asthma exacerbations are the cornerstone of the evaluation of asthma management, but severe asthma exacerbations are rare events. Therefore, trials that assess drug efficacy on exacerbations are done late in clinical development programmes. We aimed to establish an endpoint capturing clinically relevant deteriorations (diary events) that, when combined with severe exacerbations, create a composite outcome (CompEx). CompEx needs to strongly mirror results seen with the severe exacerbation-validated outcome, to allow the design of clinical trials of shorter duration and that include fewer patients than trials assessing severe exacerbations. Methods: Data from 12 asthma trials of 6 months or 12 months duration and, with standardised collection of exacerbations and diary card variables, were used to construct and test CompEx. The study populations had a mean age of 35–53 years, 59–69% were female, and had a mean FEV1 percentage of predicted normal of 63–84%. With data from five trials, we established a series of diary events based on peak expiratory flow (P), reliever use (R), symptoms (S), awakenings (A), and threshold values for change from baseline and slopes to assess trends. For the development phase, we evaluated different variable combinations and deterioration criteria to select the most robust algorithm to define a diary event for the composite outcome. We defined a composite outcome, CompEx, as first occurrence of a diary event or a severe exacerbation. We assessed the performance of CompEx in seven trials by comparing the event frequency, treatment effect (hazard ratio; HR), and the sample size needed for future trials for the CompEx versus episodes of severe exacerbations. Findings: CompEx (based on PRS) was the algorithm that best fulfilled our two-set criteria. When censored at 3 months, CompEx resulted in 2·8 times more events than severe exacerbations, and while preserving the treatment effect observed on severe exacerbations (CompEx over severe exacerbation average HR 1·01). The increased number of events, together with the sustained treatment effect, resulted in a large net gain in power, with a 67% mean reduction in the number of patients required in a drug trial for severe exacerbations. In six of seven comparisons tested, CompEx reduced the sample size needed by at least 50%. Validation of independent test populations confirmed the ability of CompEx to increase event frequencies, preserve treatment effect, and reduce the number of patients needed. Interpretation: CompEx is a composite outcome for evaluation of new asthma therapies. CompEx allows design of shorter trials that require fewer patients than studies of severe exacerbations, while preserving the ability to show a treatment effect compared with severe exacerbations. Funding: AstraZeneca.